2011
DOI: 10.3144/expresspolymlett.2011.85
|View full text |Cite
|
Sign up to set email alerts
|

Synergetic role of nanoparticles and micro-scale short carbon fibers on the mechanical profiles of epoxy resin

Abstract: Abstract. It was demonstrated in our previous work that the combined carbon nanofibers (CNFs) and microsized short carbon fibers (SCFs) in epoxy (EP) leads to significant improvements in the mechanical properties of the matrix. In this work, the effect of nano-SiO 2 particles, having an extremely different aspect ratio from CNFs, on the tensile property and fracture toughness of SCFs-filled EP was studied. It was revealed that the combined use of SCFs and silica nanoparticles exerts a synergetic effect on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(23 citation statements)
references
References 50 publications
0
23
0
Order By: Relevance
“…However, it is still uncertain how nanoparticles affect the glass transition behaviors of epoxy resins. In the literature, the glass transition temperatures (T g ) of epoxy resins have been reported to increase [1,[11][12][13], decrease [14][15][16][17][18], not change [19][20][21], or even show non-monotonic trend [22][23][24] as a function of filler content. This reflects the very complicated interactions between filler and resin, depending on numerous factors, such as type of epoxy resin and filler, surface physicochemistry of filler, filler loading, curing degree of epoxy, interfacial characters, etc.…”
Section: Introductionmentioning
confidence: 98%
“…However, it is still uncertain how nanoparticles affect the glass transition behaviors of epoxy resins. In the literature, the glass transition temperatures (T g ) of epoxy resins have been reported to increase [1,[11][12][13], decrease [14][15][16][17][18], not change [19][20][21], or even show non-monotonic trend [22][23][24] as a function of filler content. This reflects the very complicated interactions between filler and resin, depending on numerous factors, such as type of epoxy resin and filler, surface physicochemistry of filler, filler loading, curing degree of epoxy, interfacial characters, etc.…”
Section: Introductionmentioning
confidence: 98%
“…The latter is improper as already reserved to indicate composites containing two or more different reinforcements. Composites with multiscale reinforcements are typically those which contain nano-and microscale reinforcements (which may be of different types and thus also hybrids) simultaneously [49].…”
Section: Organic Fibersmentioning
confidence: 99%
“…3c), but this testing result decreases to 27. 6 after the incorporation of 12 phr Hyper E102 (Fig. 3d).…”
Section: Tensile Propertiesmentioning
confidence: 99%
“…The researchers tried to introduce a second phase into the SCFRC or modify the surfaces of SCFs to improve their toughening and reinforcing effect. For example, Zhang et al [6] introduced nanosilica particles into the SCF/EP binary system, and their experimental results showed that stress concentration around the SCF/EP interfaces, especially near the end of the fibers, was efficiently relieved. Li et al [8] successfully prepared SCFRC with Cu-coated SCFs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation